Hubungan antara pemberian makanan bergizi dan keamanan pangan: Tinjauan literatur - Kemal Suryoadji; Najma Ali; Dhanis Adrianto Setyawan; Muhammad Faruqi; Arnold Keane; Christopher Christian; Arimbi Kusuma Wardani; Rizki Fauzi Suskhan; Albertus Marcio Edbert Rompies; Keisha Annabel Garnette; Ilham Qurrota A’yun; Elza Nur Warsa Putra; Kevin Tadeus Simanjuntak (Nur Science Institute, 2025)
The Free Nutritious Meal (MBG) program aims to improve children’s nutrition and learning outcomes. However, large-scale implementation faces food safety challenges leading to foodborne illness outbreaks in Indonesia. This narrative literature review examined the relationship between nutritious meal programs and food safety risks and identified preventive measures for safer school feeding. Searches were performed in PubMed, Scopus, Cochrane, and Google Scholar using keywords related to food safety, foodborne illness, school feeding, and nutritious meals. Studies were grouped into three themes: nutritional impact, contamination risks, and prevention. Nutritious meal programs reduce stunting and improve school attendance, yet inadequate hygiene and weak supervision remain major causes of food poisoning. Key contaminants include Salmonella spp., Escherichia coli, and Bacillus cereus, associated with poor sanitation, improper storage, and untrained food handlers. The effectiveness of nutritious meal programs depends on robust food safety systems, including hygiene enforcement, regular audits, food handler training, and coordinated government oversight.